Nepal Infrastructure Sector Assessment - World Bank (World Bank, Washington, DC, 2019)
Despite several severe shocks in the past, conflict, unstable governments, earthquakes, and trade disruptions, Nepal has made strong progress in reducing poverty and boosting shared prosperity. With the decade-long peace and constitutional process concluded, the Government of Nepal is keen to accelerate economic growth and become a middle-income country by 2030. Between 1996 and 2011, the proportion of households living in extreme poverty fell from 46 to 15 percent. Nepal's macroeconomic fundamentals have remained sound. This report takes place as Nepal transitions to a federal structure. This poses a unique and unprecedented opportunity to establish clarity of functions, expenditures, and revenue assignments, as well as changing jurisdictions across various levels of governments and agencies, including as they interface with the private sector. The new government is in place and emphasizing the need for stronger cooperation between the public and private sectors. Against this background, this report assesses the energy (electricity generation, transmission, and distribution), transport (roads, airports, and urban transport), and urban (water supply, sanitation, and solid waste management) infrastructure sectors. The report recommends interventions that combine short-term and longer-term structural and policy changes with tailored project implementation approaches. Completing projects will help stress test the framework and system and identify potential bottlenecks that can be corrected. Such a learning-by-doing approach will further help prioritize the implementation of the initiatives proposed in this report and target capacity development initiatives in the areas of greatest need.